Dynamics of the geomagnetically disturbed ionosphere as measured by GPS receivers and SuperDARN HF radars - Thomas, Evan Grier (Virginia Tech, 2012)
Total electron content (TEC) data measured from ground-based GPS receivers is compared to HF backscatter from ionospheric irregularities obtained by Super Dual Auroral Radar Network (SuperDARN) radars. We present the first observations of a recurrent region of anomalous enhanced TEC at mid-latitudes over North America and attempt to characterize its frequency of occurrence. Next, we examine the relationship of convection electric fields to the formation of a polar cap tongue of ionization (TOI) from mid-latitude plumes of storm enhanced density (SED) during a geomagnetic storm on 26 September 2011. A channel of high density F region plasma was transported from the dayside ionosphere and into the polar cap by enhanced convection electric fields extending to mid-latitudes. After the solar wind IMF conditions quieted and the dayside convection electric fields retreated to higher latitudes, an SED was observed extending to, but not entering, the dayside cusp region. The source mechanism (enhanced electric fields) previously drawing the plasma from mid-latitudes and into the polar cap was no longer active, resulting in a fossil feature which persisted for several hours as it elongated in magnetic local time. Finally, we discuss ground surface effects on the HF backscatter observed by four SuperDARN radars. Monthly ground scatter occurrence rates are calculated for comparison with Arctic sea ice boundaries derived from satellite observations, showing reduced backscatter from regions covered by ice. Master of Science